FNA smears as a potential source of DNA for targeted next‐generation sequencing of lung adenocarcinomas. Issue 6 (16th February 2016) - Treece, Amanda L.; Montgomery, Nathan D.; Patel, Nirali M.; Civalier, Chris J.; Dodd, Leslie G.; Gulley, Margaret L.; Booker, Jessica K.; Weck, Karen E.
Abstract : BACKGROUND: Diff‐Quik–stained fine‐needle aspiration (FNA) smears and touch preparations from biopsies represent alternative specimens for molecular testing when cell block or biopsy material is insufficient. This study describes the use of these samples for targeted next‐generation sequencing (NGS) of primary and metastatic lung adenocarcinoma and reports the DNA quality and success rates of FNA smears versus other specimens from 1 year of clinical use. METHODS: A validation set of 10 slides from 9 patients with prior clinical epidermal growth factor receptor ( EGFR ) Sanger sequencing and KRAS pyrosequencing (5 KRAS ‐positive/ EGFR ‐negative and 4 KRAS ‐negative/ EGFR ‐negative) underwent DNA extraction, quality assessment, and targeted NGS. Subsequently, lung adenocarcinoma specimens submitted for NGS solid tumor mutation panel testing in 1 calendar year (60 biopsies, 57 resections, 33 FNA cell blocks, 12 FNA smears, and 10 body fluid cell blocks) were reviewed for specimen adequacy, sequencing success, and DNA quality. RESULTS: All 10 validation samples met the DNA quality threshold (delta Ct threshold < 8; range, –2.2 to 4.9) and yielded 0.5 to 22 μg of DNA. The KRAS and EGFR mutation status from FNA smears according to NGS was concordant with previous clinical testing for all 10 samples. In the 1‐year review, FNA smears were 100% successful, and this suggested a performance equivalent to or better than the performance of established specimen types, including FNA cell blocks. DNA quality according to ΔCt was significantly better with FNA smears versus biopsies, resections, and FNA cell blocks. CONCLUSIONS: FNA smears of lung adenocarcinomas are high‐quality alternative specimens for a targeted NGS panel with a high success rate in clinical practice. Cancer Cytopathol 2016;124:406–14 . © 2016 American Cancer Society . Abstract : Diff‐Quik–stained fine‐needle aspiration cytology smears are a source of easily extracted high‐quality DNA suitable for targeted next‐generation sequencing. In 1 year of clinical utilization, 100% of fine‐needle aspiration smears submitted for sequencing yielded adequate DNA for sequencing with equal or higher quality measures in comparison with other specimen types.